Öffentliche Räume in Pompeji - Haug, Annette (2023)
Experiencing towns means feeling atmospheres. This impact made by urban spaces depends largely on their architecture and its decorative and visual features – including its design. In this sense, this volume is about aesthetic, semantic, and functional design strategies in ancient Pompeii and the impact they had on urban actors.